DIPLOMASI INDONESIA DALAM MENYIKAPI TUDUHAN DUMPING KERTAS FOTOCOPY A4 OLEH AUSTRALIA PERIODE 2016-2020 - Adinda Rizky Islamiati (2021)
Paper is used for writing, printing, wrapping and so on. Paper is one of the leading exports of forest products for Indonesia to the Australian market. Australia is a profitable paper export destination and is a source of foreign exchange for Indonesia. However, in 2016 Indonesia's paper exports experienced obstacles to the Australian market, where Australia accused of dumping Indonesian A4 photocopy paper. In addition, Australia stipulates anti-dumping import duties on A4 photocopy paper from Indonesia. This study aims to determine the diplomatic efforts carried out by the Government of Indonesia in responding to allegations of dumping A4 photocopy paper by Australia. The researcher uses the concept of diplomacy to analyze the diplomatic efforts carried out by the Indonesian Government to resolve allegations of dumping A4 photocopy paper by Australia which brings the Indonesian Government's interest in reopening paper market access to Australia. Then the researcher uses the theory of international trade related to tariff barriers to see the trade barriers that occur between Indonesia and Australia which are included in the anti-dumping tariff barriers. The researcher also uses the concept of dumping to look at the dumping accusations given by Australia to Indonesian paper producers. The use of qualitative research methods with a case study approach was chosen by the researchers to describe the accusations of dumping A4 photocopy paper by Australia to Indonesian paper producers and the efforts made by the Indonesian government in resolving the dumping allegations. The results of this study indicate that the diplomacy carried out by the Indonesian government has succeeded in reopening access to the Indonesian paper market to Australia and Indonesian paper exports to Australia have increased. Diplomacy carried out by the Government of Indonesia is coordinating and communicating with stakeholders and the Australian Government, filing a lawsuit on allegations of paper dumping to the WTO, sending an official letter to the Australian Government and a comprehensive framework for cooperation between Indonesia and Australia in eliminating paper import duties.